Endotracheal tube-induced sore throat pain and inflammation is coupled to the release of mitochondrial DNA. Issue 1 (September 2017) - Puyo, Carlos A; Peruzzi, Daniela; Earhart, Alexander; Roller, Evan; Karanikolas, Menelaos; Kollef, Marin H; Krupnick, Alexander S; Kreisel, Daniel; Ibrahim, Mohsen; Gelman, Andrew E
In the absence of infection, the pathophysiology of endotracheal tube-induced sore throat pain is unclear. Activated neutrophils release elastase, reactive oxygen species, and inflammatory cytokines known to contribute to neuropathic pain. Sterile tissue injury can cause the release of damage-associated molecular patterns such as mitochondrial DNA that promote neutrophil activation. We hypothesized that endotracheal tube-induced sore throat pain is linked to mitochondrial DNA-mediated neutrophil inflammation. A nonrandomized prospective survey for sore throat pain was conducted in 31 patients who required short-term intubation and had no evidence of upper airway infection. Patterns of neutrophil abundance, activation, and mitochondrial DNA levels were analyzed in tracheal lavage fluid following intubation and prior to extubation. Thirteen of 31 patients reported sore throat pain. Sore throat patients had high neutrophilia with elevated adhesion molecule and TLR9 expression and constitutive reactive oxygen species generation. Tracheal lavage fluid from sore throat patients accumulated mitochondrial DNA and stimulated neutrophils to release mediators associated with pain in a TLR9- and DNAse-dependent fashion. Endotracheal tube-induced sore throat is linked to the release of mitochondrial DNA and can drive TLR9-mediated inflammatory responses by neutrophils reported to cause pain. Mitigating the effects of cell-free mitochondrial DNA may prove beneficial for the prevention of endotracheal tube-mediated sore throat pain.